Atuação de assistentes sociais na área socioambiental : subsídios para o trabalho profissional - Caetano, Marina (2021)
In this doctoral dissertation, we reflect upon the socio-environmental topic and its articulation to Social Work, a profession based contradictions of capitalist production system expressed by manifestations of the socio-environmental issue. We address the environment degradation, which is deeply bound to such production system that uses natural resources to produce goods. The relationship between humanity and nature takes place based on an understanding that man is constituted of nature, about which he does his work via work activity, work object, and the means of work. From the 1960s and 1970, organizations from around the world started looking differently to the environment, with greater attention and care, surrounded by some contradictions, though. Events and discussions directed to the environmental issue started in several countries, where authorities have reflected and came into terms through documents on a reduction of the environmental degradation. Movements related to the environmental prevention and protection occupied the world stage. This dissertation is justified by the need of addressing some socio-environmental issues and the relationship to Social Work in the capitalist scenario, focused on the elaboration of interventional subsidies in the field in face of socio-environmental issue manifestations. In face of the approximation of social workers to issues related to environment, we consider this study relevant to Social Work, amplifying the discussion in the professional category. It is in this sense that the present research aims to answer the following problem: What are the necessary subsidies to the profession work of social workers in face of manifestations of the socio-environmental issue? The general objective is to elaborate interventional subsidies capable of guiding the work of social workers in the socio-environmental field, in order to contribute to the production of knowledge in Social Work. Therefore, we seek to problematize the social worker’s work at the elaboration of these subsidies. The dissertation is based on the method of historical-dialectical materialism. It is qualitative research, and exploratory and descriptive in nature. To collect data, we used semi-structured interviews. Seven is the number of subjects involved in the study, five of them work on Social Work and in social policies, and two of them are professionals of other areas and represent social-environmental organizations. To analyze data, we have conducted a content analysis. One of the conclusions achieved is that Social Work works in an interdisciplinary way in the socio-environmental field, aiming to point interventional horizons for these professionals in the socio-environmental field.